HUBUNGAN TINGKAT PENGETAHUAN IBU DAN DUKUNGAN SUAMI TERHADAP KEBERHASILAN PEMBERIAN ASI EKSKLUSIF - Eka Putri Primasari (JURNAL KESEHATAN MERCUSUAR, 2019)
Abstract: Breast milk is the best food for babies, especially in the first month of life. Breast milk contains all nutrients to build and provide the energy needed by the baby. The low rate of breastfeeding is a threat to child development. Several factors related to the success of exclusive breastfeeding are the level of knowledge of the mother and husband's support. The purpose of this study was to determine the relationship between the level of knowledge of mothers and husband's support towards the success of exclusive breastfeeding in Lubuk Kilangan Puskesmas in 2017. This study was analytical with a cross sectional design. The population in this study amounted to 153 respondents. A sample of 31 respondents obtained by simple ramdom sampling. Data were analyzed bivariate. The statistical test results obtained p-value = 0,000. It can be concluded that there is a relationship between the knowledge of mothers about exclusive breastfeeding and husband's support for the success of exclusive breastfeeding.